In-orbit performance of avalanche photodiode as radiation detector on board the picosatellite Cute-1.7+APD II - Kataoka, J.; Toizumi, T.; Nakamori, T.; Yatsu, Y.; Tsubuku, Y.; Kuramoto, Y.; Enomoto, T.; Usui, R.; Kawai, N.; Ashida, H.; Omagari, K.; Fujihashi, K.; et al. (Journal of Geophysical Research Atmospheres, 2010)
The Cute‐1.7+APD II, 10 × 15 × 20 cm3 in size and 5 kg in mass, is the third picosatellite developed by students at the Tokyo Institute of Technology. One of the primary goals of the Cute‐1.7+APD II mission is to validate the use of avalanche photodiodes (APDs) as a radiation detector for the first time in a space experiment. While the mission itself is immature compared to the forefront satellites of space plasma physics, use of APDs offers various possibilities regarding a brand‐new electron energy analyzer for medium‐energy electrons and ions (1–100 keV), as well as a high‐performance light sensor for the future X‐ray astronomy missions. The satellite was successfully launched by ISRO PSLV‐C9 rocket on 28 April 2008 and has since been in operation for more than a year. The Cute‐1.7+APD II carries two reverse‐type APDs to monitor the distribution of low‐energy particles (mainly electrons and protons) down to 9.2 keV trapped in a low Earth orbit (LEO), including the South Atlantic Anomaly (SAA) as well as aurora bands. We present the design parameters and various preflight tests of the APDs prior to launch, particularly, the high counting response and active gain control system for the Cute‐1.7+APD II mission. Examples of electron/proton distribution, obtained in continuous 12 h observations, will be presented to demonstrate the initial flight performance of the APDs in orbit.